Preparing Co/N-Doped Carbon as Electrocatalyst toward Oxygen Reduction Reaction via the Ancient “Pharaoh’s Snakes” Reaction - Jian Gao; Mengxin Zhou; Xinyao Wang; Hong Wang; Zhen Yin; Xiaoyao Tan; Yuan Li (Batteries, 2022)
The oxygen reduction reaction (ORR) is of great importance for clean energy storage and conversion techniques such as fuel cells and metal–air batteries (MABs). However, the ORR is kinetically sluggish, and expensive noble metal catalysts are required. The high price and limited preservation of noble metal catalysts has largely hindered the wide application of clean power sources such as fuel cells and MABs. Therefore, it is important to prepare non-expensive metal catalysts (NPMC) to cut the price of the fuel cells and MABs for wide application. Here, we report the preparation of a Co3O4 carried on the N-doped carbon (Co/N-C) as the ORR NPMC with a facile Pharaoh’s Snakes reaction. The gas generated during the reaction is able to fabricate the porous structure of the resultant carbon doped with heteroatoms such as Co and N. The catalyst provides a high electrocatalytic activity towards ORR via the 4-e pathway with an onset and half-wave potential of 0.98 and 0.79 V (vs. RHE), respectively, in an electrolyte of 0.1 M KOH. The onset and half-wave potentials are close to those of the commercial Pt/C. This work demonstrates the promising potential of an ancient technology for preparing NPMCs toward the ORR.